Designing Lessons for Differentiated Learning Using Moodle LMS - Jamaluddin J.E.; Abidin I.Z.; Azree Idris M.; Masrom U.K. (American Institute of Physics Inc., 2023)
Students can lose attention and gain minimal understanding once teachers use a single instructional strategy despite the various students' learning styles. The students' lack of engagement is improved by implementing differentiated learning. Universiti Tenaga Nasional, in its blended learning initiative, explores the possibilities to provide differentiated learning via its Moodle learning management system. The suitability of using Moodle LMS to provide differentiated learning needs to be studied. A study is done for EECB423 Data Communication and Network course to propose the process of designing learning paths via Lesson activity. The design of the learning paths, which is based on flowcharts, use contents in various forms such as videos, quizzes and reading tasks. The flowcharts are seen to be helpful in guiding the teachers to align and link topics and to provide assessment in a way that enhances students' learning experience. 2022 American Institute of Physics Inc.. All rights reserved.